2013
DOI: 10.1530/jme-13-0015
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mRNA expression of arcuate nucleus appetite-regulating peptides during lactation in rats

Abstract: The contribution of hypothalamic appetite-regulating peptides to further hyperphagia accompanying the course of lactation in rats was investigated by using PCR array and real-time PCR. Furthermore, changes in the mRNA expression for appetite-regulating peptides in the hypothalamic arcuate nucleus (ARC) were analyzed at all stages of pregnancy and lactation, and also after weaning. Food intake was significantly higher during pregnancy, lactation, and after weaning than during non-lactation periods. During lacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 79 publications
2
14
1
1
Order By: Relevance
“…In the present study, AgRP mRNA expression was significantly up-regulated in striped hamsters raising larger litter sizes, whereas NPY, POMC and CART mRNA expression did not differ between the hamsters raising different litter sizes. This is partly consistent with the observation that in lactating rats, both NPY and AgRP are greatly elevated (Chen et al, 2004;Crowley et al, 2004;Li et al, 1999;Malabu et al, 1994;Pickavance et al, 1999;Smith, 1993;Suzuki et al, 2014), but the increase in AgRP mRNA expression during lactation is especially marked (Suzuki et al, 2014). POMC and/or CART mRNA expression significantly decreased during lactation in comparison with the non-lactation period (Brogan et al, 2000;Smith, 1993;Sorensen et al, 2002;Suzuki et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, AgRP mRNA expression was significantly up-regulated in striped hamsters raising larger litter sizes, whereas NPY, POMC and CART mRNA expression did not differ between the hamsters raising different litter sizes. This is partly consistent with the observation that in lactating rats, both NPY and AgRP are greatly elevated (Chen et al, 2004;Crowley et al, 2004;Li et al, 1999;Malabu et al, 1994;Pickavance et al, 1999;Smith, 1993;Suzuki et al, 2014), but the increase in AgRP mRNA expression during lactation is especially marked (Suzuki et al, 2014). POMC and/or CART mRNA expression significantly decreased during lactation in comparison with the non-lactation period (Brogan et al, 2000;Smith, 1993;Sorensen et al, 2002;Suzuki et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…The neuroendocrine basis of hyperphagia in lactation is suggested to be triggered by hypothalamic neuropeptides, such as the orexigenic neuropeptides NPY and AgRP, and the anorexigenic neuropeptides POMC and CART (Brogan et al, 2000;Chen et al, 2004;Crowley et al, 2004;Malabu et al, 1994;Li et al, 1999;Pickavance et al, 1999;Smith, 1993;Sorensen et al, 2002;Suzuki et al, 2014). In the present study, AgRP mRNA expression was significantly up-regulated in striped hamsters raising larger litter sizes, whereas NPY, POMC and CART mRNA expression did not differ between the hamsters raising different litter sizes.…”
Section: Discussioncontrasting
confidence: 51%
“…The data suggest a signaling mechanism linking adiposity, hypothalamic neuropeptide gene expression, and intestinal growth, where the latter two changes may act to increase energy assimilation to counteract the energy loss in the adipose tissue. In fact, energy restriction, lactation, and cold exposure, each of which reduces adiposity and plasma leptin, also increased energy intake and the intestinal weight (8,30,40,46). By changing the protein to WPI, and bearing in mind the effect on the intestinal mechanisms of energy absorption and presumed energy loss, the above effects of the low sucrose were accentuated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that circulating leptin levels are lowered in lactating rats compared with nonlactating animals (Denis et al 2003). Moreover, lactation is associated with reduced expression of anorexigenic POMC and increased expression of orexigenic AGRP and NPY (Suzuki et al 2014). Since leptin, POMC, AGRP, and NPY affect the KP/GnIH-GnRH system, they can also modulate Rfrp and Kiss1 expression during lactation.…”
Section: Kp and Gnih Signaling In Conditions Of Altered Energy Balancmentioning
confidence: 99%